Effect of biomechanical footwear on upper and lower leg muscle activity in comparison with knee brace and normal walking. (April 2021) - Ylinen, Jari; Pennanen, Antti; Weir, Adam; Häkkinen, Arja; Multanen, Juhani
Abstract: Aim: To evaluate the activity of knee stabilizing muscles while using custom-made biomechanical footwear (BF) and to compare it when walking barefoot and with a knee brace (Unloader®). Methods: Seventeen healthy working-aged (mean age: 29 years; standard deviation: 8 years) individuals participated. The knee brace was worn on the right knee and BF in both legs. Surface electromyography (sEMG) data was recorded bilaterally from vastus medialis (VM), semitendinosus (ST), tibialis anterior (TA) and lateral gastrocnemius (LG) muscles during walking, and repeated-measures ANOVA with a post-hoc t -test was used to determine differences between the different walking modalities (barefoot, brace and BF). Results: Averaged sEMG was significantly higher when walking with BF than barefoot or knee brace in the ST muscles, in the right LG, and left TA muscle. It was significantly lower when walking with the brace compared to barefoot in the right ST and LG muscles, and left TA muscle. Analysis of the ensemble-averaged sEMG profiles showed earlier activation of TA muscles when walking with BF compared to other walking modalities. Conclusion: BF produced greater activation in evaluated lower leg muscles compared to barefoot walking. Thus BF may have an exercise effect in rehabilitation and further studies about its effectiveness are warranted.